Application of flow sensitive gradients for improved measures of metabolism using hyperpolarized 13c MRI. Issue 3 (6th May 2015) - Gordon, Jeremy W.; Niles, David J.; Adamson, Erin B.; Johnson, Kevin M.; Fain, Sean B.
Abstract : Purpose: To develop the use of bipolar gradients to suppress partial‐volume and flow‐related artifacts from macrovascular, hyperpolarized spins. Theory and Methods: Digital simulations were performed over a range of spatial resolutions and gradient strengths to determine the optimal bipolar gradient strength and duration to suppress flowing spins while minimizing signal loss from static tissue. In vivo experiments were performed to determine the efficacy of this technique to suppress vascular signal in the study of hyperpolarized [1‐ 13 C]pyruvate renal metabolism. Results: Digital simulations showed that in the absence of bipolar gradients, partial‐volume artifacts from the vasculature were still present, causing underestimation of the apparent reaction rate of pyruvate to lactate ( kP ). The addition of a bipolar gradient with b = 32 s/mm 2 sufficiently suppressed the vascular signal without a substantial decrease in signal from static tissue. In vivo results corroborate digital simulations, with similar peak lactate signal to noise ratio (SNR) but substantially different kP in the presence of bipolar gradients. Conclusion: The proposed approach suppresses signal from flowing spins while minimizing signal loss from static tissue, removing contaminating signal from the vasculature and increasing kinetic modeling accuracy without substantially sacrificing SNR or temporal resolution. Magn Reson Med 75:1242–1248, 2016. © 2015 Wiley Periodicals, Inc.